THE IMPACT OF TIME MANAGEMENT SKILLS ON PROCRASTINATION IN STUDENTS (Universal International Scientific Journal, 2026)
This article analyzes the impact of time management skills on the level of procrastination in students. Factors such as time planning, prioritization, and self-control are associated with procrastination of academic tasks. It also shows that students with developed time management skills have lower levels of procrastination and that developing time management skills is an important psychological factor in reducing procrastination.
Keywords: time management, procrastination, academic performance, self-control, motivation, planning, prioritization, student personality, socio-psychological factors, efficiency.